2012
DOI: 10.1155/2012/175146
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Investigation of the Ring Strain Energy, Destabilization Energy, and Heat of Formation of CL-20

Abstract: The cage compound CL-20 (a.k.a., 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane, HNIW, or 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazatetracyclo[5.5.0.03,11.05,9]dodecane) is a well-studied high-energy-density material (HEDM). The high positive gas- (ΔfHg°) and solid- (ΔfHs°) phase heat of formation values for CL-20 conformers have often been attributed to the strain energy of this cage compound and, by implication, to the conventional ring strain energy (CRSE) inherent in isowurtzitane which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Two sets of 298 H f Δ (g) values for 1-6 are given in Table 3. Together with cyclic nitramines, the noncyclic nitramines, nitro compounds, and two cage molecules (adamantane and urotropin) were used as the reference species in the isodesmic reactions ( Table 2, reactions [10][11][12][13][14][15][16][17][18][19]. The reactions used in Refs.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Two sets of 298 H f Δ (g) values for 1-6 are given in Table 3. Together with cyclic nitramines, the noncyclic nitramines, nitro compounds, and two cage molecules (adamantane and urotropin) were used as the reference species in the isodesmic reactions ( Table 2, reactions [10][11][12][13][14][15][16][17][18][19]. The reactions used in Refs.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The density of nitramines increases with increasing molecular rigidity [ 11 ]. One notable example is hexanitro-2,4,6,8,10,12-hexaazatetracyclo[5.5.0.0 3,11 .0 5,9 ]dodecane (hexanitrohexaazaisowurtzitane, CL-20) ( Figure 1 ), which exhibits one of the highest detonation velocities (V 0 D = 9.36 (ε) km/s) among all of the explosives, and the highest density among the known nitranmines (ρ = 2.044 g/cm 3 ) [ 12 , 13 , 14 , 15 ], as well as a positive enthalpy of formation (ΔH f = 454 kJ/mol), optimal oxygen balance (−11.0) and detonation pressure (420 kbar) [ 16 , 17 , 18 , 19 , 20 , 21 ]. CL-20 excels compared to the other high-energy explosive materials such as HMX, RDX, PETN, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This is reflected in the heats of formation for these species, which are: 1.09 kJ g À1 (ONC) [5] > 0.97 kJ g À1 (CL-20) [6] > 0.25 kJ g À1 (HMX) [7]. A recent study [8] has shown that all of the additional energy exhibited by these cage species comes directly from the strain due to the cage structure. In the case of ONC, the cubane framework is responsible for the majority of the energy, whereas in CL-20 it is the resulting or enhanced strain among the NO 2 ligands [8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study [8] has shown that all of the additional energy exhibited by these cage species comes directly from the strain due to the cage structure. In the case of ONC, the cubane framework is responsible for the majority of the energy, whereas in CL-20 it is the resulting or enhanced strain among the NO 2 ligands [8]. While there has been a significant amount of work on the use of cage structures for fuels [2-6, 8, 9], none have been investigated as potential oxidizers.…”
Section: Introductionmentioning
confidence: 99%